A string theory of quantum gravity and inertial fields for the description of reality - Levi, Daniel (Open Science Journal, 2023)
Relativity of space time neglects uncertainty principle while Quantum Mechanics takes into account the uncertainty principle but neglects space time structure. In this work we put both principles together and find one expression for the interval to the type of Kaluza Klein where the fifth term is not one extra dimension but a quantum state of space. This work is complementary with others where posit a model of vacuum in which decompose the continuous spatial geometry into 3-dimensional cells and put a oscillator in each one. This oscillators couple in a way that build a large set of open and closed fibers that group in open strings. Because this strings have no null section, it can be interpreted as a extra dimension. We will show in a self consistent way that this cells model can explain gravity and inertial forces in algebraic terms.